IV Bienal de Arte de Panama : Cerveceria Nacional. - Museo de Arte Contemporaneo? eL dORADO; Bienal de Arte Panama 1998; Arias, Alfredo; Escoffery, Irene; Kupfer, Mónica E.; Oviero, Ramón; Perez-Ratton, Virginia; Pini, Ivonne; Sullivan, Edward (Panamá : Cerveceria Nacional, S.A., 1998)
Aranda, Iris Nelia ; Arcia, Roy Alberto ; Bornéo, Josiane ; Castillo, Alberto ; Ceville, Raúl ; Duarte, José Inocente ; Espino, Raúl ; Fajardo, Eric ; Fallenbaum, Jack ; Garuz, Ana Elena ; Jaén, Rdorigo ; March, Jorge ; Martinez-Uliten, Carlos ; Martinez, Victor ; Matos, Brasilio ; Mezza, Guillermo ; Milson, Lezlie ; Montilla, Manuel ; Navarro, Eduardo ; Prudhoe, Lisa ; Quintero, Gilberto ; Rodaniche, Carlos E. ; Rodriguez, Efrain ; Rodriguez, Evene ; Rodriguez, Franklin ; Rojas, Sergio ; Sanchez, Desiderio ; Suescum, Haydée Victoria ; Toledo, Fernando ; Ramos, Aristides Ureña ; Vamvas, Spiros ; Velarde, Dickey ; Zelenka, Rodney ; Zhukov, Emily
biografie
IV Bienal de Arte de Panama : Cerveceria Nacional, Museo de Arte Contemporaneo, Panama City, Junio - Julio 1998
Spaans
boek